ABREACTION REVISITED TREATMENT OF PTSD BY ABREACTION - Kaiser, Fawad; Dewan, Hamayon B (Journal of Pakistan Psychiatric Society, 2006)
This paper describes the successful treatment of a 38year old man with a three months history of PTSD.The distressing dreams began shortly after the October earthquake after he had witnessed his familymembers dying under the collapsed roof. Previous psychiatric treatment including psychotherapy hadfailed to bring about any improvement. Abreaction was induced by the oral administration of sodiumamytal and methylphenidate. Patient was interviewed on more than one occasions while he was underthe influence of these drugs. After six sessions the nightmares stopped and normal sleep was restored.Two months after his discharge from the clinic there had been no recurrence. Drug-induced abreactionis a valuable technique in particular clinical cases. By using the oral route, its complications andinconveniences can be reduced.Key words: Posttraumatic Stress Disorder, nightmares, abreaction